Caldesmon controls stress fiber force-balance through dynamic cross-linking of myosin II and actin-tropomyosin filaments - Kokate, Shrikant B.; Ciuba, Katarzyna; Tran, Vivien D.; Kumari, Reena; Tojkander, Sari; Engel, Ulrike; Kogan, Konstantin; Kumar, Sanjay; Lappalainen, Pekka (Nature Communications, 2022)
Contractile actomyosin bundles are key force-producing and mechanosensing elements in muscle and non-muscle tissues. Whereas the organization of muscle myofibrils and mechanism regulating their contractility are relatively well-established, the principles by which myosin-II activity and force-balance are regulated in non-muscle cells have remained elusive. We show that Caldesmon, an important component of smooth muscle and non-muscle cell actomyosin bundles, is an elongated protein that functions as a dynamic cross-linker between myosin-II and tropomyosin-actin filaments. Depletion of Caldesmon results in aberrant lateral movement of myosin-II filaments along actin bundles, leading to irregular myosin distribution within stress fibers. This manifests as defects in stress fiber network organization and contractility, and accompanied problems in cell morphogenesis, migration, invasion, and mechanosensing. These results identify Caldesmon as critical factor that ensures regular myosin-II spacing within non-muscle cell actomyosin bundles, and reveal how stress fiber networks are controlled through dynamic cross-linking of tropomyosin-actin and myosin filaments.
Gesehen am 19.12.2022